Positive and Negative Regulatory Roles of C-Terminal Src Kinase (CSK) in FcεRI-Mediated Mast Cell Activation, Independent of the Transmembrane Adaptor PAG/CSK-Binding Protein - Potuckova, Lucie; Draberova, Lubica; Halova, Ivana; Paulenda, Tomas; Draber, Petr (Frontiers in immunology, 2018)
C-terminal Src kinase (CSK) is a major negative regulator of Src family tyrosine kinases (SFKs) that play critical roles in immunoreceptor signaling. CSK is brought in contiguity to the plasma membrane-bound SFKs via binding to transmembrane adaptor PAG, also known as CSK-binding protein. The recent finding that PAG can function as a positive regulator of the high-affinity IgE receptor (FcεRI)-mediated mast cell signaling suggested that PAG and CSK have some non-overlapping regulatory functions in mast cell activation. To determine the regulatory roles of CSK in FcεRI signaling, we derived bone marrow-derived mast cells (BMMCs) with reduced or enhanced expression of CSK from wild-type (WT) or PAG knockout (KO) mice and analyzed their FcεRI-mediated activation events. We found that in contrast to PAG-KO cells, antigen-activated BMMCs with CSK knockdown (KD) exhibited significantly higher degranulation, calcium response, and tyrosine phosphorylation of FcεRI, SYK, and phospholipase C. Interestingly, FcεRI-mediated events in BMMCs with PAG-KO were restored upon CSK silencing. BMMCs with CSK-KD/PAG-KO resembled BMMCs with CSK-KD alone. Unexpectedly, cells with CSK-KD showed reduced kinase activity of LYN and decreased phosphorylation of transcription factor STAT5. This was accompanied by impaired production of proinflammatory cytokines and chemokines in antigen-activated cells. In line with this, BMMCs with CSK-KD exhibited enhanced phosphorylation of protein phosphatase SHP-1, which provides a negative feedback loop for regulating phosphorylation of STAT5 and LYN kinase activity. Furthermore, we found that in WT BMMCs SHP-1 forms complexes containing LYN, CSK, and STAT5. Altogether, our data demonstrate that in FcεRI-activated mast cells CSK is a negative regulator of degranulation and chemotaxis, but a positive regulator of adhesion to fibronectin and production of proinflammatory cytokines. Some of these pathways are not dependent on the presence of PAG.
Keywords: C-terminální Src kinasa; fibronektiny; Analysis of Variance; Calcium; receptory IgE; SHP-1; CSK Tyrosine-Protein Kinase; Mice, Knockout; HEK293 buňky; Mast Cells; STAT5 Transcription Factor; Protein Tyrosine Phosphatase, Non-Receptor Type 6; vápník; fosforylace; buňky kostní dřeně; membránové proteiny; Receptors, IgE; cytokiny; signální transdukce; Membrane Proteins; Genetic Vectors; Phosphorylation; HEK293 Cells; fosfoproteiny; transkripční faktor STAT5; Cell Degranulation; src-Family Kinases; Phosphoproteins; Signal Transduction; LYN; tyrosin; degranulace buněk; myši knockoutované; skupina kinas odvozených od src-genu; Intercellular Signaling Peptides and Proteins; Animals; lidé; mezibuněčné signální peptidy a proteiny; analýza rozptylu; STAT5; Humans; zvířata; mastocyty; C-terminal Src kinase; Tyrosine; myši inbrední C57BL; myši; genetické vektory; Mice, Inbred C57BL; degranulation; tyrosinfosfatasa nereceptorového typu 6; Cytokines; cytokines; Mice; Fibronectins; Bone Marrow Cells; phosphoprotein associated with glycosphingolipid-enriched microdomains; mast cell